Bacteriophage P1 protein Icd inhibits bacterial division by targeting FtsZ - Zhao, Kairui; Du, Shuheng; Tian, Linlin; Wang, Shenping; Shi, Runqin; Sun, Haiyu; Zhou, Yao; Huang, Chenhao; Sun, Yanmei; Wang, Shiwei; Chen, Yaodong (Frontiers in Microbiology, 2025)
The study of bacteriophage (phage) gene products and their effects on the host helps to better understand the phage-host relationship and provides clues for the development of new antimicrobial proteins. In this study, we focused on a small protein named Icd with 73 amino acids from phage P1. It inhibits the growth of Escherichia coli and rapidly blocks the formation of Z-ring. The results of bacterial two-hybrid and pull-down experiments showed that Icd directly targets FtsZ, a key protein in bacterial division. Furthermore, we identified the core region of Icd as amino acids 12–51; this 40-amino acid protein had similar antibacterial activity to the full-length Icd, inhibiting bacterial growth and division.